2013
DOI: 10.1155/2013/387508
|View full text |Cite
|
Sign up to set email alerts
|

Impediments for the Uptake of the Botswana Government′s Male Circumcision Initiative for HIV Prevention

Abstract: Botswana remains one of the countries with high prevalence of HIV infection with a population prevalence rate of 17.6 in 2008. In 2009, the Ministry of Health launched male circumcision as an additional strategy to the already existing HIV preventive efforts. The purpose of this paper is to share what the participants of a survey to evaluate a short-term male circumcision communication strategy in seven health districts of Botswana reported as impediments for the program's uptake. Qualitative data were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 11 publications
(19 reference statements)
2
17
1
Order By: Relevance
“…Despite the efficacy of male circumcision in reducing female‐to‐male transmission of HIV and STIs (WHO/UNAIDS Technical Consultation on Male Circumcision and HIV Prevention, ), only 5% of the teenagers who were aged 15–19 years in Botswana have been circumcised because this is not part of the Botswana culture, thus losing the benefit of this prevention strategy. Currently, the uptake is slow because of inadequate knowledge about its safety, especially for older men, the fear of pain, and criteria of selecting only HIV‐negative men (Sabone et al , , ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the efficacy of male circumcision in reducing female‐to‐male transmission of HIV and STIs (WHO/UNAIDS Technical Consultation on Male Circumcision and HIV Prevention, ), only 5% of the teenagers who were aged 15–19 years in Botswana have been circumcised because this is not part of the Botswana culture, thus losing the benefit of this prevention strategy. Currently, the uptake is slow because of inadequate knowledge about its safety, especially for older men, the fear of pain, and criteria of selecting only HIV‐negative men (Sabone et al , , ).…”
Section: Introductionmentioning
confidence: 99%
“…These findings concur with the belief that intensification of neonatal circumcision is better because it is associated with fewer medical risks (29). Other studies have mainly sited poor knowledge of health care workers in relation to VMMC and the need for HIV testing (30).…”
Section: Discussionmentioning
confidence: 99%
“…There is need to dispel some myths, attitudes and beliefs about safe male circumcision which may fuel risky behaviours. Sabone et al (2013) observed that some wrong beliefs, myths and attitudes are key impediments to uptake of safe male circumcision among men in Botswana. They (Sabone et al, 2013) suggested the need for further information, education and communication about SMC to reduce the level to which risk compensation could moderate the protective effects of SMC.…”
Section: Discussionmentioning
confidence: 99%